New scan compression approach to reduce the test data volume - Pralhadrao V. Shantagiri; Rohit Kapur; Chandrasekar Shastry (IET Computers & Digital Techniques)
Abstract The test data volume (TDV) increases with increased target compression in scan compression and adds to the test cost. Increased TDV is the result of a dependency across scan flip‐flops (SFFs) that resulted from compression architecture, which is absent in scan mode. The SFFs have uncompressible values logic‐0 and logic‐1 in many or most of the patterns contribute to the TDV. In the proposed new scan compression (NSC) architecture, SFFs are analysed from Automatic Test Pattern Generation (ATPG) patterns generated in a scan mode. The identification of SFFs to be moved out of the compression architecture is carried out based on the NSC. The method includes a ranking of SFFs based on the specified values present in the test patterns. The SFFs having higher specified values are moved out of the compression architecture and placed in the outside scan chain. The NSC is the combination of scan compression and scan mode. This method decides the percentage (%) of SFFs to be moved out of compression architecture and is less than 0.5% of the total SFFs present in the design to achieve a better result. The NSC reduces dependencies across the SFFs present in the test compression architecture. It reduces the TDV and test application time. The results show a significant reduction in the TDV up to 78.14% for the same test coverage.